Analisis Selisih Data Nilai Tinggi Hasil Pengukuran Lapangan Terhadap Nilai Tinggi Orthometrik DEMNAS di D.I.R. Belanti Kabupaten Tapin - Syauqi, Ucu; Shodiq, Adib Muhammad (Jurnal Teknologi Berkelanjutan, 2025)
Based on the reference field used, there are two known geodetic height systems: the geometric geodetic height system and the physical geodetic height system. Several types of height are recognized, including normal height, orthometric height, and dynamic height. Elevation data from the national digital elevation model (DEMNAS) will be supplemented with field leveling (waterpass) measurements to obtain elevation values at the survey control points in the area. The differences between field data and DEMNAS data will be calculated to determine the discrepancies in orthometric height at those points. The report was prepared using data processing methods from field measurements conducted in the survey area. The research focuses on determining the orthometric height at benchmark points within the study location, which is in Binuang, Tapin Regency, South Kalimantan. Leveling was carried out using a round-trip method corrected according to Indonesian National Standards (SNI), resulting in elevation data. In addition, GNSS observations were conducted using geodetic GPS with the static method to obtain corrected coordinates and orthometric height. Data from DEMNAS was processed using ArcMap 10.3 software to produce interpolated elevation values, such as at BM 04, which showed a height of 3.303 meters. By comparing DEMNAS data and field survey data, differences in elevation were found between BM 18 and BM 22. The discrepancies were as follows: BM 18 = -2.160 meters and BM 22 =-0.682 meters.